Negative electrode material, preparation method and sodium ion battery
By designing the product of the specific surface area and true density of the negative electrode material within a specific range, and using the combination of hard carbon and carbon cladding and closed pores, the problem of insufficient capacity and voltage platform of the negative electrode material of sodium ion battery is solved, achieving higher energy density and output power.
Patent Information
- Application Number
- CN202411929572.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The negative electrode material of existing sodium ion batteries has a low gram capacity and charge and discharge voltage platform, which limits the energy density and output voltage of sodium ion batteries.
A negative electrode material is provided, whose product of specific surface area A and true density B meets A×B <8, and the closed pore ratio and disorder are regulated through the combination of hard carbon and carbon cladding and closed pores, thereby increasing the capacity.
The energy density and average discharge voltage of sodium ion batteries are improved, the output power is enhanced, and the problems of low gram capacity and energy density in the prior art are overcome.
Smart Images

Figure CN119674034A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and in particular relates to a negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] Sodium-ion batteries have the advantages of low price, moderate energy density, good low temperature and rate performance, so they are widely used in low-speed electric vehicles, start-stop power supplies, energy storage, etc. However, since the energy density of sodium-ion batteries is significantly lower than that of lithium-ion batteries, the application of sodium-ion batteries is significantly limited.
[0003] Research has found that improving the gram capacity and charge-discharge voltage platform of sodium-ion battery negative electrode materials can significantly increase the energy density of sodium-ion batteries and improve their output voltage and power, thereby greatly improving user experience. Therefore, it is very important to improve the gram capacity and charge-discharge voltage platform of sodium-ion battery negative electrode materials. However, the gram capacity and charge-discharge voltage platform of sodium-ion battery negative electrode materials reported and applied in the prior art are generally low, which limits the application of the energy density of sodium-ion batteries. Summary of the invention
[0004] In view of the above problems in the prior art, the first aspect of the present application provides a negative electrode material, wherein the specific surface area A and the true density B of the negative electrode material satisfy A×B<8; preferably A×B<6; more preferably A×B<4. When A×B of the negative electrode material is within the above range, it is ensured that the true density and specific surface area are controlled within a certain range, thereby ensuring the pore volume and compacted density and gram capacity of the negative electrode material.
[0005] In some embodiments of the present application, the specific surface area A of the negative electrode material is 0.5 m 2 / g-6m 2 / g; preferably 0.9m 2 / g-5m 2 / g; more preferably 1m 2 / g-4m 2 The negative electrode material has a specific surface area within the above range, which can ensure that the closed porosity of the negative electrode material is high.
[0006] In some embodiments of the present application, the true density B of the negative electrode material is 0.5 g / m 3 -1.45g / m 3 ; preferably 0.8g / m 3 -1.4g / m 3 More preferably 0.95 g / m 3 -1.3g / m 3True density can also be called skeleton density. The true density is tested with nitrogen as the medium. Since there are a large number of closed pores inside the negative electrode material particles, nitrogen cannot enter these closed pores during testing. The negative electrode material has a true density within the above range, which means that the closed porosity of the negative electrode material is high, resulting in a high closed pore volume.
[0007] The negative electrode material provided in the present application includes hard carbon and a carbon coating layer and closed pores coating the hard carbon, wherein the closed pores are formed by open pores in which the carbon coating layer completely coats the outer surface of the hard carbon, and the closed pore volume accounts for more than 90% of the sum of all open pore volume and closed pore volume; preferably, the closed pore volume accounts for more than 95% of the sum of all open pore volume and closed pore volume; more preferably, the closed pore volume accounts for more than 99% of the sum of all open pore volume and closed pore volume.
[0008] In some embodiments of the present application, the closed-pore pore size of the negative electrode material is less than 3 nm; preferably 0.1 nm-3 nm; preferably 0.5 nm-3 nm; more preferably 1 nm-3 nm.
[0009] In some embodiments of the present application, the negative electrode material I d / I g The range is 1.0-2.0; preferably, the negative electrode material I d / I g The range is 1.3-1.6. d The value indicates that the negative electrode material has a Raman spectrum of 1350±50cm -1 The intensity of the characteristic peak D near I g The value indicates that the negative electrode material has a Raman spectrum of 1580±50cm -1 The intensity of the characteristic peak G near I d / I g The value of represents the disorder of the material. The larger the ratio, the higher the disorder. The closed pore volume of the negative electrode material will increase the disorder of the negative electrode material. d / I g The value of ensures that the disorder degree of the negative electrode material is improved.
[0010] In some embodiments of the present application, the position of the diffraction peak in the X-ray diffraction spectrum of the negative electrode material is in the range of 20° to 30° at 2θ, and the half-peak width of the diffraction peak is 3° to 10°; preferably, the diffraction peak position of the negative electrode material is in the range of 24° to 25°, and the half-peak width is 3° to 4°. The high disorder of the negative electrode material can be tested by X-ray diffraction method. The negative electrode material has only one diffraction peak in the above numerical range because the disorder of the negative electrode material is high, the internal microcrystals are randomly arranged, and the interlayer spacing is disorderly distributed.
[0011] According to the second aspect of the present application, the present application provides a method for preparing the negative electrode material, which includes but is not limited to the following steps: regulating the closed porosity and disorder of the negative electrode material by changing at least one of the hard carbon precursor raw materials and pore-forming agent substances, changing the sintering treatment temperature, increasing the water activation step, and changing the number of carbon coating treatments, thereby adjusting the gram capacity.
[0012] In some embodiments of the present application, the preparation method includes but is not limited to the following steps:
[0013] S1, obtaining initial raw materials: uniformly mixing one or more precursor raw materials with the required pore-forming agent;
[0014] S2, obtaining a first precursor: sintering and heat-insulating the initial raw material under a protective atmosphere;
[0015] S3, obtaining the second precursor: purifying and screening the first precursor;
[0016] S4, obtaining a negative electrode material: carbon-coating the second precursor to obtain a negative electrode material.
[0017] In some embodiments of the present application, in step S2, the entire process is carried out under a protective atmosphere, and when a water activation step is added during the heat preservation treatment, the protective atmosphere is switched to water vapor for heat preservation and activation.
[0018] In some embodiments, the protective atmosphere is an inert gas; in some embodiments, the inert gas includes but is not limited to at least one of nitrogen, argon, helium, neon, krypton and xenon; preferably, the inert gas is nitrogen.
[0019] In some embodiments of the present application, the precursor raw materials of step S1 include but are not limited to one or a mixture of any several of resin-based precursors, petroleum-based precursors and biomass-based precursors; in some embodiments, the precursor raw materials include but are not limited to epoxy resin, phenolic resin, polyfurfuryl alcohol, polyvinyl alcohol, polythiophene, petroleum coke, asphalt, coal, fruit shell, lignin, sodium lignin sulfonate, glucose, starch, tannic acid one or a mixture of any several; the pore-forming agent includes but is not limited to one or a mixture of any several of hexadecyltrimethylammonium bromide, melamine, styrene, biphenyl, naphthalene, potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, sodium amide, sodium dihydrogen phosphate, and ammonium hydrogen phosphate.
[0020] In some embodiments of the present application, the precursor raw material and the pore-forming agent of step S1 are mixed in a certain ratio, and the mixing ratio of the precursor and the pore-forming agent is a mass ratio of (50-150): (50-150); preferably, the mixing ratio of the precursor and the pore-forming agent is a mass ratio of (80-120): (80-120); more preferably, the mixing ratio of the precursor and the pore-forming agent is a mass ratio of (95-100): (95-100).
[0021] In some embodiments of the present application, the sintering temperature of step S2 may be 700°C-1000°C; preferably, the sintering temperature of step S2 may be 750°C-800°C; more preferably, the sintering temperature of step S2 is 800°C. In some embodiments of the present application, the heating rate of the sintering temperature of step S2 may be 3°C / min-10°C / min; preferably, the heating rate of the sintering temperature of step S2 may be 5°C / min-7 / min.
[0022] In some embodiments of the present application, the carbon coating treatment includes at least one carbon coating; preferably, the carbon coating treatment is a double carbon coating treatment. In some embodiments of the present application, the carbon coating treatment includes a gas phase carbon coating treatment; specifically, a gas atmosphere required for carbon coating is introduced at a certain temperature to open pores on the surface of the hard carbon negative electrode material to deposit carbon, and the open pores are coated to form closed pores, and the formation of closed pores enhances its sodium storage capacity.
[0023] In some embodiments of the present application, the carbon-coating gas atmosphere includes a gaseous hydrocarbon carbon source, which is but not limited to at least one of methane, acetylene, ethylene, ethane, propane, propylene, propyne, acetone and benzene.
[0024] In some embodiments of the present application, the carbon coating process may include introducing a gaseous hydrocarbon carbon source at a certain temperature for a first carbon coating for a certain period of time; preferably, the carbon coating process may include introducing a gaseous hydrocarbon carbon source at a certain temperature for a first carbon coating for a certain period of time, then switching to another gaseous hydrocarbon carbon source atmosphere for a second carbon coating for a certain period of time.
[0025] According to the third aspect of the present application, the present application provides a negative electrode plate, which includes a binder, a thickener, the negative electrode material and a negative electrode collector, or the negative electrode plate includes a binder, a thickener, the negative electrode material obtained by the preparation method and a negative electrode collector.
[0026] In some embodiments of the present application, the 1540.25 mm 2The negative electrode sheet has an average coating weight (CW) of 30 mg-200 mg of the negative electrode material coated on the surface of the negative electrode sheet, a thickness (h) of 0.039 mm-0.433 mm, and a CW / h of 900-1600.
[0027] According to the fourth aspect of the present application, the present application provides an electrochemical device, comprising the negative electrode sheet described in the third aspect; the electrochemical device is a sodium ion battery.
[0028] According to a fifth aspect of the present application, the present application provides an electronic device, characterized in that the electronic device includes the electrochemical device described in the fourth aspect.
[0029] The negative electrode material provided in the present application adopts a specific precursor and a specific double coating preparation method, so that the closed porosity of the negative electrode material obtained in this case reaches more than 90%. The higher closed porosity makes the closed pore volume larger and the disorder degree larger, and its sodium storage capacity is improved. The prepared sodium ion battery has a higher capacity and energy density. In addition, it also has a higher average discharge voltage. The sodium ion battery has a higher output power. The present application overcomes the problem of low gram capacity and energy density of sodium ion batteries in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM schematic diagram of the negative electrode material provided in Example 3 of the present application. DETAILED DESCRIPTION
[0031] The technical solution of the present application is further described below through specific examples and comparative examples, and the specific examples do not limit the protection scope of the present application. Some non-essential modifications and adjustments made by others based on the concept of the present application still fall within the protection scope of the present application.
[0032] For simplicity, for a certain parameter, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unclearly recorded range, and any lower limit can also be combined with other lower limits to form an unclearly recorded range, and any upper limit can also be combined with any other upper limits to form an unclearly recorded range. In addition, each separately disclosed point or single value itself can be used as a lower limit or upper limit and combined with any other point or single value or with other lower limits or upper limits to form an unclearly recorded range.
[0033] In the description herein, unless otherwise specified, “above” and “below” include the number.
[0034] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0035] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0036] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "include" and "comprises" and similar expressions are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units that are not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.
[0037] The terms used in this application have the conventional meanings in the art, such as:
[0038] Open pores refer to the pore structure on the surface of porous materials that is accessible to fluids and communicates with the outside world.
[0039] Closed pores refer to porous materials that are coated with carbon materials, for example, so that the open pores on the surface become pore structures that are inaccessible to fluids and are not connected to the outside world.
[0040] The closed porosity refers to the percentage of closed pores in the total amount of all open and closed pores.
[0041] The pore former refers to an additive that creates a pore structure in a material, and can be mixed with a hard carbon precursor material to form a pore structure in the hard carbon material.
[0042] According to the first aspect of the present application, the present application provides a negative electrode material, wherein the specific surface area A and the true density B of the negative electrode material satisfy A×B<8; preferably A×B<6; more preferably A×B<4. When A×B of the negative electrode material is within the above range, it is ensured that the true density and the specific surface area are controlled within a certain range, thereby ensuring the pore volume and compacted density and gram capacity of the negative electrode material.
[0043] In some embodiments of the present application, the specific surface area A of the negative electrode material is 0.5 m 2 / g-6m 2 / g; preferably 0.9m 2 / g-5m 2 / g; more preferably 1m 2 / g-4m 2 / g. For example, the specific surface area of the negative electrode material can be 0.5m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, 5.5m 2 / g, 6m 2 / g or a range consisting of any two of the above values. The negative electrode material has a specific surface area within the above range, which can ensure that the closed porosity of the negative electrode material is high.
[0044] In some embodiments of the present application, the true density B of the negative electrode material is 0.5 g / m 3 -1.45g / m 3 ; preferably 0.8g / m 3 -1.4g / m 3 More preferably 0.95 g / m 3 -1.3g / m 3 For example, the true density of the negative electrode material can be 0.5 g / m 3 , 0.6g / m 3 , 0.7g / m 3 , 0.8g / m 3 , 0.9g / m 3 1.0g / m 3 , 1.1g / m 3 , 1.2g / m 3 , 1.3g / m 3 , 1.4g / m 3 1.45g / m3 Or a range consisting of any two of the above values. True density is also called skeleton density. True density is tested with nitrogen as the medium. Since there are a large number of closed pores inside the negative electrode material particles, nitrogen cannot enter these closed pores during testing. The negative electrode material has a true density in the above range, which means that the closed porosity of the negative electrode material is high, so that its closed pore volume is high.
[0045] The negative electrode material includes hard carbon, a carbon coating layer covering the hard carbon, and closed pores, wherein the closed pores are formed by the open pores on the outer surface of the hard carbon covered by the carbon coating layer, and the closed pore volume accounts for more than 90% of the sum of all open pore volumes and closed pore volumes. Preferably, the closed pore volume accounts for more than 95% of the sum of all open pore volumes and closed pore volumes; more preferably, the closed pore volume accounts for more than 99% of the sum of all open pore volumes and closed pore volumes. When the proportion of closed pores is high, the skeleton density of the negative electrode material is low and the sodium storage capacity is strong.
[0046] In some embodiments of the present application, the closed pore size of the negative electrode material is less than 3nm; preferably 0.1nm-3nm; preferably 0.5nm-3nm; more preferably 1nm-3nm. Specifically, the closed pore size of the negative electrode material can be 0.1nm, 0.5nm, 1.0nm, 1.1nm, 1.2nm, 1.3nm, 1.4nm, 1.5nm, 1.6nm, 1.7nm, 1.8nm, 1.9nm, 2.0nm, 2.1nm, 2.2nm, 2.3nm, 2.4nm, 2.5nm, 2.6nm, 2.7nm, 2.8nm, 2.9nm, 3.0nm or a range consisting of any two of the above values. By adjusting the closed pore size of the negative electrode material, the negative electrode material can have a suitable closed pore volume.
[0047] In some embodiments of the present application, the negative electrode material I d / I g The range is 1.0-2.0; preferably, the negative electrode material I d / I g The range is 1.3-1.6; specifically, I d / I g The value of can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or a range consisting of any two of the above values. d The value indicates that the negative electrode material has a Raman spectrum of 1350±50cm -1 The intensity of the characteristic peak D nearby is caused by the radial breathing mode of the symmetric stretching vibration of the sp2 carbon atoms in the aromatic ring; I g The value indicates that the negative electrode material has a Raman spectrum of 1580±50cm-1 The intensity of the characteristic peak G near the I is caused by the stretching vibration between sp2 carbon atoms; d / I g The value of represents the disorder of the material. The larger the ratio, the higher the disorder. The increase in the closed pore volume of the negative electrode material will increase the disorder of the negative electrode material. d / I g The value of ensures that the disorder degree of the negative electrode material is improved.
[0048] In some embodiments of the present application, the position of the diffraction peak in the X-ray diffraction spectrum of the negative electrode material is in the range of 20° to 30° at 2θ, and the half-peak width of the diffraction peak is 3° to 10°; preferably, the diffraction peak position of the negative electrode material is in the range of 24° to 25°, and the half-peak width is 3° to 4°. The high disorder of the negative electrode material can be tested by X-ray diffraction method. The negative electrode material has only one diffraction peak in the above numerical range because the disorder of the negative electrode material is high, the internal microcrystals are randomly arranged, and the interlayer spacing is disorderly distributed.
[0049] According to the second aspect of the present application, the present application provides a method for preparing the negative electrode material, which includes but is not limited to the following steps: regulating the closed porosity and disorder of the negative electrode material by changing at least one of the hard carbon precursor raw materials and pore-forming agent substances, changing the sintering treatment temperature, increasing the water activation step, and changing the number of carbon coating treatments, thereby adjusting the gram capacity.
[0050] In some embodiments of the present application, the preparation method includes but is not limited to the following steps:
[0051] S1, obtaining initial raw materials: uniformly mixing one or more precursor raw materials with the required pore-forming agent;
[0052] S2, obtaining a first precursor: sintering and heat-insulating the initial raw material under a protective atmosphere;
[0053] S3, obtaining the second precursor: purifying and screening the first precursor;
[0054] S4, obtaining a negative electrode material: carbon-coating the second precursor to obtain a negative electrode material.
[0055] In some embodiments of the present application, in step S2, the entire process is carried out under a protective atmosphere, and when a water activation step is added during the heat preservation treatment, the protective atmosphere is switched to water vapor for heat preservation and activation.
[0056] In some embodiments, the protective atmosphere is an inert gas; in some embodiments, the inert gas includes but is not limited to at least one of nitrogen, argon, helium, neon, krypton and xenon; preferably, the inert gas is nitrogen.
[0057] In the above preparation method, the closed porosity and disorder of the negative electrode material are regulated by changing at least one of the hard carbon precursor raw material and pore-forming agent material, changing the sintering treatment temperature, adding a water activation step, and changing the number of carbon coating treatments. For example, changing the hard carbon precursor raw material and pore-forming agent material can change the specific surface area and disorder, and change the gram capacity; selecting a suitable sintering temperature can change the ratio of the specific surface area and skeleton density of the negative electrode material and the closed pore diameter. Too high or too low a temperature will lead to a decrease in the final gram capacity and energy density; during the heat preservation process after the sintering treatment, adding a water activation step can effectively increase the closed pore diameter and disorder of the negative electrode material, so that the final gram capacity and energy density are effectively enhanced; increasing one carbon coating to two carbon coatings can significantly reduce the specific surface area and skeleton density of the negative electrode material, and ensure that the ratio of the two is within a certain range, the disorder increases, and the closed porosity and pore volume of the negative electrode material increase, and the final gram capacity and energy density are effectively increased.
[0058] In some embodiments of the present application, the precursor raw materials of step S1 include but are not limited to one or a mixture of any several of resin-based precursors, petroleum-based precursors and biomass-based precursors; in some embodiments, the precursor raw materials include but are not limited to epoxy resin, phenolic resin, polyfurfuryl alcohol, polyvinyl alcohol, polythiophene, petroleum coke, asphalt, coal, fruit shell, lignin, sodium lignin sulfonate, glucose, starch, tannic acid one or a mixture of any several; the pore-forming agent includes but is not limited to one or a mixture of any several of hexadecyltrimethylammonium bromide, melamine, styrene, biphenyl, naphthalene, potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, sodium amide, sodium dihydrogen phosphate, and ammonium hydrogen phosphate.
[0059] In some embodiments of the present application, the precursor raw material and the pore-forming agent of step S1 are mixed in a certain ratio, and the mixing ratio of the precursor and the pore-forming agent is a mass ratio of (50-150): (50-150); preferably, the mixing ratio of the precursor and the pore-forming agent is a mass ratio of (80-120): (80-120); more preferably, the mixing ratio of the precursor and the pore-forming agent is a mass ratio of (95-100): (95-100).
[0060] In some embodiments of the present application, the sintering temperature of step S2 may be 700°C-1000°C; preferably, the sintering temperature of step S2 may be 750°C-800°C; more preferably, the sintering temperature of step S2 is 800°C. Specifically, the sintering temperature may be 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, or a range consisting of any two of the above values.
[0061] In some embodiments of the present application, the heating rate of the sintering temperature in step S2 may be 3°C / min-10°C / min; preferably, the heating rate of the sintering temperature in step S2 may be 5°C / min-7 / min. Specifically, the heating rate of the sintering temperature in step S2 may be 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or a range consisting of any two of the above values.
[0062] In some embodiments of the present application, the heat preservation treatment time of step S2 is 1h-10h; preferably, the heat preservation treatment time of step S2 is 1h-4h. Specifically, the heat preservation treatment time of step S2 is 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or a range consisting of any two of the above values.
[0063] In some embodiments of the present application, the carbon coating treatment includes at least one carbon coating; preferably, the carbon coating treatment is a double carbon coating treatment. In some embodiments of the present application, the carbon coating treatment includes a gas phase carbon coating treatment; specifically, a gas atmosphere required for carbon coating is introduced at a certain temperature to open pores on the surface of the hard carbon negative electrode material to deposit carbon, and the open pores are coated to form closed pores, and the formation of closed pores enhances its sodium storage capacity.
[0064] In some embodiments of the present application, the carbon-coating gas atmosphere includes a gaseous hydrocarbon carbon source, which is but not limited to at least one of methane, acetylene, ethylene, ethane, propane, propylene, propyne, acetone and benzene.
[0065] In some embodiments of the present application, the carbon coating process may include introducing a gaseous hydrocarbon carbon source at a certain temperature for a first carbon coating for a certain period of time; preferably, the carbon coating process may include introducing a gaseous hydrocarbon carbon source at a certain temperature for a first carbon coating for a certain period of time, then switching to another gaseous hydrocarbon carbon source atmosphere for a second carbon coating for a certain period of time.
[0066] In some embodiments of the present application, the temperature of the carbon coating may be 800°C-1500°C; preferably, the temperature of the carbon coating may be 800°C-1200°C; specifically, the temperature of the carbon coating may be 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or a range consisting of any two of the above values.
[0067] In some embodiments of the present application, the carbon coating time may be 1-10 h; preferably, the carbon coating time may be 2-5 h; specifically, the carbon coating time may be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or a range consisting of any two of the above values.
[0068] According to the third aspect of the present application, the present application provides a negative electrode plate, which includes a binder, a thickener, the negative electrode material and a negative electrode collector, or the negative electrode plate includes a binder, a thickener, the negative electrode material obtained by the preparation method and a negative electrode collector.
[0069] In some embodiments of the present application, the 1540.25 mm 2 The negative electrode sheet has an average coating weight (CW) of 30 mg-200 mg of the negative electrode material coated on the surface of the negative electrode sheet, a thickness (h) of 0.039 mm-0.433 mm, and a CW / h of 900-1600.
[0070] In some embodiments of the present application, the binder includes but is not limited to any one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon.
[0071] In some embodiments of the present application, the thickener includes but is not limited to at least one of carboxymethyl cellulose (sodium), hydroxymethyl cellulose, methyl cellulose, ethyl cellulose, polyvinyl alcohol, polyacrylic acid (ester), oxidized starch, phosphorus-oxidized starch, casein, etc.
[0072] In some embodiments of the present application, the negative electrode current collector includes but is not limited to any one of copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, and a polymer substrate coated with a conductive metal, or any combination thereof.
[0073] In some embodiments of the present application, the negative electrode active material layer further includes a conductive agent, which includes but is not limited to carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof; in some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof; in some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0074] According to a fourth aspect of the present application, the present application provides an electrochemical device, comprising a negative electrode sheet according to any of the aforementioned embodiments.
[0075] In some embodiments, the electrochemical device includes, but is not limited to, a sodium ion battery.
[0076] In some embodiments of the present application, the sodium ion battery provided by the present application includes a negative electrode sheet, a positive electrode sheet, an electrolyte, and a separator between the positive electrode and the negative electrode sheet as in any of the aforementioned embodiments. Therefore, the sodium ion battery provided by the present application has a higher gram capacity and energy density.
[0077] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material, a binder, and a conductive carbon additive located on the surface of the positive electrode current collector.
[0078] The present application has no particular restrictions on the positive electrode current collector, positive electrode active material, conductive agent and binder, as long as they can achieve the purpose of the present application.
[0079] In some embodiments, the positive electrode current collector may include aluminum foil, aluminum alloy foil, etc. In some embodiments, the positive electrode active material may include a layered oxide (such as NaCu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O 2 ), Prussian blue series (such as NaFe[Fe(CN) 6 ] or Na 2 Fe[Fe(CN) 6 ]), or at least one of a polyanion compound (such as sodium vanadium phosphate); in some embodiments, the thickness of the positive electrode collector is 5 μm to 20 μm, preferably 6 μm to 18 μm, and the thickness of the positive electrode active material layer is 30 μm to 120 μm; in some embodiments, the mass ratio of the positive electrode active material, the positive electrode conductor and the positive electrode binder in the positive electrode active material layer is (94 to 98): (0.5 to 2.5): (1.5 to 3.5).
[0080] The present application has no particular limitation on the electrolyte, as long as the purpose of the present application can be achieved; in some embodiments, the electrolyte may include a sodium salt and a non-aqueous solvent; in some embodiments of the present application, the sodium salt may include at least one of sodium perchlorate or sodium hexafluorophosphate (NaPF6); in some embodiments, the non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents, or a combination thereof; in some embodiments, the carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound, or a fluorinated carbonate compound; in some embodiments, the The linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC); in some embodiments, the cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC); in some embodiments, the fluorinated carbonate compound may include but is not limited to fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate (FCC ... At least one of ester, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate; in some embodiments, the carboxylate compound may include but is not limited to methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valerolactone, mevalonolactone or caprolactone. at least one of; in some embodiments, the ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran; in some embodiments, the other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate.
[0081] The present application has no particular restrictions on the isolation membrane, as long as the purpose of the present application can be achieved; in some embodiments, the material of the isolation membrane includes but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of the membrane may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0082] In some embodiments, the sodium ion battery of the present application further comprises a packaging bag, in which the electrolyte, the positive electrode plate, the separator and the negative electrode plate are contained. The present application has no particular limitation on the packaging bag, which may be a packaging bag known in the art, as long as the purpose of the present application can be achieved; in some embodiments, the packaging bag may be an aluminum-plastic film or a steel shell.
[0083] According to a fifth aspect of the present application, the present application provides an electronic device, characterized in that the electronic device includes the electrochemical device.
[0084] The present application does not particularly limit the electronic device, which can be any electronic device known in the prior art; in some embodiments, the electronic device can include but is not limited to drones, laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, etc.
[0085] The present application is described in more detail below through examples.
[0086] Example 1
[0087] Embodiment 1 provides a negative electrode material, which includes hard carbon, a carbon coating layer covering the hard carbon, and closed pores, wherein the closed pores are formed by pore openings formed by the carbon coating layer covering the outer surface of the hard carbon.
[0088] The preparation method of the negative electrode material comprises the following steps:
[0089] (1) Obtaining initial raw materials: Weighing 100 g of petroleum coke raw material and 100 g of potassium hydroxide, and mixing them evenly in a shear mixer to obtain initial raw materials;
[0090] (2) Preparation of a first precursor: In a nitrogen atmosphere, the initial raw material is heated to a first temperature of 800° C. at a heating rate of 5° C. / min, and the nitrogen atmosphere is continued to be maintained. The first temperature of 800° C. is kept constant for 2 h for sintering, and then the temperature is naturally lowered to obtain a first precursor;
[0091] (3) Preparation of the second precursor: The first precursor was washed several times with 1M hydrochloric acid, dried, and then subjected to air flow crushing and classification, and particle size screening to obtain the second precursor;
[0092] (4) Carbon coating to obtain the final negative electrode material: In a nitrogen atmosphere, the second precursor was heated to a second temperature of 900°C at a heating rate of 5°C / min, and the atmosphere was switched to CH 4 After 4 hours of heat preservation, the atmosphere was switched to C 2 H 2 After keeping warm for 2 hours, the temperature starts to cool down automatically to obtain the final negative electrode material.
[0093] Example 2
[0094] The negative electrode material provided in Example 2 is different from the negative electrode material in Example 1 in that in Example 2, the initial raw material component is changed from raw petroleum coke to medium-temperature asphalt, and the other steps are exactly the same as in Example 1.
[0095] Example 3
[0096] The negative electrode material provided in Example 3 is different from the negative electrode material in Example 1 in that, in the preparation method of Example 3, the atmosphere kept at a constant temperature of 800°C for 2 hours during the preparation of the first precursor is replaced by nitrogen with water vapor, and the other steps are exactly the same as in Example 1.
[0097] Example 4
[0098] The negative electrode material provided in Example 4 is different from the negative electrode material in Example 2 in that, in the preparation method of Example 4, the atmosphere kept at a constant temperature of 800°C for 2 hours during the preparation of the first precursor is replaced by nitrogen with water vapor, and the other steps are exactly the same as in Example 2.
[0099] Example 5
[0100] The negative electrode material provided in Example 5 is different from the negative electrode material in Example 1 in that in Example 5, the initial raw material component changes the raw material petroleum coke to a mixture of petroleum coke and glucose (the mass ratio of petroleum coke to glucose is 1:2), and the other steps are exactly the same as in Example 1.
[0101] Example 6
[0102] The negative electrode material provided in Example 6 is different from the negative electrode material in Example 3 in that in Example 6, the initial raw material component changes the raw material petroleum coke to a mixture of petroleum coke and glucose (the mass ratio of petroleum coke to glucose is 1:2), and the other steps are exactly the same as in Example 3.
[0103] Example 7
[0104] The negative electrode material provided in Example 7 is different from the negative electrode material in Example 3 in that, in Example 7, potassium hydroxide in the initial raw material component is replaced with sodium hydroxide, and the other steps are exactly the same as in Example 3.
[0105] Example 8
[0106] The negative electrode material provided in Example 8 is different from the negative electrode material in Example 4 in that, in Example 8, potassium hydroxide in the initial raw material component is replaced with sodium hydroxide, and the other steps are exactly the same as in Example 4.
[0107] Example 9
[0108] The negative electrode material provided in Example 9 is different from the negative electrode material in Example 3 in that, in Example 9, potassium hydroxide in the initial raw material component is replaced with potassium carbonate, and the other steps are exactly the same as in Example 3.
[0109] Example 10
[0110] The negative electrode material provided in Example 10 is different from the negative electrode material in Example 1 in that, in Example 10, potassium hydroxide in the initial raw material component is replaced with potassium carbonate, and the other steps are exactly the same as in Example 1.
[0111] Embodiment 11
[0112] The negative electrode material provided in Example 11 is different from the negative electrode material in Example 3 in that, in the preparation method of Example 11, the first temperature in the preparation process of the first precursor is changed from 800°C to 750°C, and the other steps are exactly the same as those in Example 3.
[0113] Example 12
[0114] The negative electrode material provided in Example 12 is different from the negative electrode material in Example 3 in that, in the preparation method of Example 12, the first temperature in the preparation process of the first precursor is changed from 800° C. to 900° C., and the other steps are exactly the same as those in Example 3.
[0115] Comparative Example 1
[0116] The negative electrode material provided in Comparative Example 1 is different from the negative electrode material in Example 1 in that, in the carbon coating stage of Comparative Example 1, the two carbon coatings are changed to only one CH 4 The other steps are exactly the same as those in Example 1.
[0117] Comparative Example 2
[0118] The negative electrode material provided in Comparative Example 2 is different from the negative electrode material in Example 2 in that, in the carbon coating stage of Comparative Example 2, the two carbon coatings are changed to only retaining one CH 4 The other steps are exactly the same as those in Example 2.
[0119] Negative electrode sheet and sodium-ion battery assembly
[0120] The negative electrode materials provided in the above-mentioned Examples 1 to 12 and the negative electrode materials provided in Comparative Examples 1 to 2 are respectively assembled into negative electrode sheets and sodium ion batteries according to the following methods:
[0121] Negative electrode sheet: The negative electrode active material (i.e., the negative electrode material provided in the above-mentioned Examples 1 to 12 and the negative electrode material provided in Comparative Examples 1 to 2), binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a mass ratio of 97:2:1 in an appropriate amount of solvent deionized water to form a negative electrode slurry with a solid content of 40 wt%; the negative electrode slurry is coated on a negative electrode current collector aluminum foil with a thickness of 10 μm, dried at 85°C, and after cold pressing, cutting, slitting, and vacuum drying at 120°C for 12 hours, a negative electrode sheet is obtained.
[0122] Positive electrode sheet: The positive electrode active material NaCu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O 2 , conductive carbon black (SuperP) as a positive electrode conductive agent, and polyvinylidene fluoride (PVDF) as a positive electrode binder were mixed in a mass ratio of 97:1.4:1.6, N-methylpyrrolidone (NMP) was added as a solvent, and the mixture was stirred thoroughly to obtain a positive electrode slurry with a solid content of 72wt% and a uniform system. The positive electrode slurry was evenly coated on the surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 85°C to obtain a positive electrode sheet.
[0123] Electrolyte: In dry (H 2In an argon atmosphere glove box with a concentration of 0<1ppm), ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed in a mass ratio of 50:50, and 1,3-propane sultone and fluoroethylene carbonate are added, dissolved and fully stirred, and then sodium salt sodium hexafluorophosphate is added, and the electrolyte is obtained after mixing evenly. Among them, based on the mass of the electrolyte, the mass percentage of 1,3-propane sultone in the electrolyte is 1.5%, the mass percentage of fluoroethylene carbonate in the electrolyte is 2%, the mass percentage of sodium hexafluorophosphate in the electrolyte is 11%, and the rest is EC and DEC.
[0124] Isolation membrane: The isolation membrane includes a 7 μm thick polyethylene (PE) substrate and 1 μm thick alumina ceramic layers respectively disposed on two surfaces of the substrate along its thickness direction. The total thickness of the isolation membrane is 9 μm.
[0125] Sodium ion battery assembly: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive and negative electrodes to play an isolating role, then wind and weld the pole ears, place them in the outer packaging foil aluminum-plastic film, inject electrolyte, and go through vacuum packaging, standing, formation, shaping, capacity testing and other processes to obtain a soft-pack sodium ion battery.
[0126] Performance Testing
[0127] The negative electrode materials, the assembled negative electrode plates and the electrochemical properties of the sodium ion batteries in the above embodiments were tested under the following test conditions, and the test results are shown in Tables 1-3.
[0128] (1) BET test method: The test method for specific surface area refers to GB / T 19587-2017. The specific process is to weigh 1g to 8g of the negative electrode material sample (the sample weight should at least cover 1 / 3 of the volume of the sphere) and place it in a 1 / 2-inch long tube with a bulb (the diameter of the spherical part is 12mm). After pretreatment at 200℃ for 2h, place it in the test equipment TriStar3030 (Mike Company, USA) for testing. The adsorption gas used is N 2 (Purity: 99.999%), the test conditions were carried out at 77K, and the specific surface area was tested by the BET calculation method.
[0129] (2) Gas volumetric method for testing the skeleton density (true density) of negative electrode materials: Place the accurately weighed negative electrode material in the sample chamber of a true density tester (AccuPyc II 1345, USA) of known volume, fill the sample chamber with nitrogen as the medium, gradually pressurize it to a specified value (19.50 psi) in the measuring chamber, and then diffuse the nitrogen into the expansion chamber. The equilibrium pressure of the two processes is automatically recorded by the instrument. The volume of the sample can be calculated based on the pressure before and after gas diffusion according to the Boyle-Malior law, and thus the true density can be calculated.
[0130] (3) Pore diameter test: The pore diameter of the hard carbon without coating treatment was measured using the Micromeritics TriStar II Plus 3030 three-station specific surface and porosity analyzer as the closed pore diameter of the hard carbon (since closed pores are formed after coating, the closed pore diameter cannot be obtained by gas adsorption test). The specific process is as follows: 1g to 8g of the hard carbon sample before coating (the sample weight should at least cover 1 / 3 of the volume of the sphere) was placed in a 1 / 2-inch long tube with a bulb (the diameter of the spherical part is 12mm), pretreated at 200℃ for 2h, and then placed in the test equipment for testing. The adsorption and desorption gas used was N 2 (Purity: 99.999%), the test conditions are carried out at 77K, and the adsorption-desorption curve is obtained. The data obtained are simulated using the advanced non-local density functional theory (NLDFT) model to obtain the pore size distribution of the material; the pore volume corresponding to each pore size can be calculated by the cumulative pore volume; the above test process is used to test the open pore volume of the coated hard carbon.
[0131] (4) Raman surface defect test: Select an area of 100μm×100μm on the negative electrode active material layer, and use a laser microscopic confocal Raman spectrometer (Raman, HR Evolution, HORIBA Scientific Instruments Division) to scan the particles in the area to obtain the D peak and G peak of all particles within the area. Use LabSpec software to process the data, and after deducting the substrate, obtain the peak intensity of the D peak and G peak of each particle, which are Id and Ig respectively, and divide them to obtain their ratio Id / Ig. The laser wavelength of the Raman spectrometer can be in the range of 532nm to 785nm. The Id / Ig value in this article is the average value of the Id and Ig ratio of all particles measured within this range. D peak: generally at 1350±50cm -1 Nearby, caused by the radial breathing mode of the symmetric stretching vibration of the sp2 carbon atoms in the aromatic ring (structural defect); G peak: appears at 1580±50cm -1 Nearby, it is caused by the stretching vibration between sp2 carbon atoms, which corresponds to the vibration of E2g optical phonon (in-plane vibration of carbon atoms) in the center of the Brillouin zone.
[0132] (5) X-ray diffraction (XRD) test: X-ray powder diffractometer (XRD, instrument model: Bruker D8 ADVANCE) was used to test the negative electrode material, with Cu Kα as the target material; the voltage and current were 40 KV / 40 mA, the scanning angle range was 10° to 80°, the scanning step length was 0.00836°, and the time per step was 0.3 s. After obtaining the raw data, the base was deducted, and the angle corresponding to the peak of the broad peak in the range of 10 to 30° was taken as the position of the 002 peak; half of the difference between the right intensity and the left intensity at the 1 / 2 intensity of the peak was taken as the half-peak width.
[0133] (6) Compacted density test: The test standard for powder compaction refers to GB / T 24533-2009 "Graphite negative electrode materials for lithium-ion batteries". The specific test method is to weigh 1.0000±0.0500g of the sample and place it in the test mold (CARVER#3619 (13mm), and then place the sample in the test equipment, the test equipment is Sansi Zongheng UTM7305, and the test tonnage is 5.0 tons. The calculation formula of compacted density is: compacted density = negative electrode material mass / negative electrode material force area / negative electrode material sample thickness.
[0134] (7) CW / h test: Take the negative electrode sheet and cut it into 1540.25mm 2 Weigh 10 small discs of the same size, deduct the weight of the current collector aluminum foil of the same size, and obtain the average coating weight (CW, in mg) of the active material in the 10 small discs. If double-sided coating is used, divide the average weight of the active material by 2 to obtain the average coating weight (CW). Then measure the thickness h of the coated active material layer in mm, where the thickness is the thickness of the double-layer coated pole piece.
[0135] (8) Sodium ion battery button test (C and D): The negative electrode sheet preparation method is used to obtain a negative electrode sheet having the negative electrode material of each embodiment, and then punched into a raw sheet with a diameter of 14 mm. After weighing the weight (weighing the corresponding empty copper foil area to obtain the weight of the substrate) and calculating the weight of the negative electrode material (negative electrode active substance), start assembling the button battery. The button battery is assembled with the obtained negative electrode sheet as the working electrode and the metal sodium sheet as the counter electrode. The two are aligned up and down and separated by an isolation membrane, and the electrolyte (the electrolyte used in the above-mentioned sodium ion battery preparation) is added dropwise to form a button battery. After the button battery is assembled, it is left to stand for 8 hours before starting the test. It is first discharged at a constant current density of 25 mA / g to 0V vs Na + / Na, and then discharged at 0V constant voltage to a current density of 2.5mA / g, and recorded the gram capacity of this step; then charged at a current density of 25mA / g to 1.5V vs Na + / Na, for the obtained charge capacity, take the gram capacity of 0-0.15V as C, and take the gram capacity of 0-1V as D.
[0136] (9) Sodium ion battery cycle performance test: The sodium ion batteries in each embodiment and comparative example were kept at a test temperature of 25°C for 5 minutes, then charged at a constant current of 1C to a voltage of 3.95V, and then charged at a constant voltage of 0.05C; discharged at a constant current of 1C to a voltage of 1.5V, which was recorded as one cycle, and the capacity at this time was recorded as D0. This cycle was repeated for 800 times, and the last discharge capacity was recorded as D1; after cycling at 25°C, the capacity decay rate was D1 / D0, in %. Five samples were tested for each embodiment or comparative example, and the average value was taken.
[0137] (10) Sodium ion battery weight energy density and average discharge voltage test: In an environment of 25°C, the sodium ion battery is charged at a constant current of 0.2C to a voltage of 3.95V, and then charged at a constant voltage to 0.02C; discharged at a constant current of 0.2C to a voltage of 1.5V, which is recorded as one cycle, and the discharge capacity and discharge energy of the first cycle are recorded; the discharge energy is divided by the discharge capacity to obtain the average discharge voltage; and the sodium ion battery weight at 50% SOC is tested to obtain the weight of the sodium ion battery. Energy density = discharge capacity × average discharge voltage / sodium ion battery weight.
[0138] Table 1 Performance test of negative electrode materials prepared in various embodiments and comparative examples
[0139]
[0140] Table 2 Performance test of negative electrode materials prepared in various embodiments and comparative examples
[0141] Example Id / Ig XRD position (°) XRD half peak width (°) Example 1 1.50 24.6 3.5 Example 2 1.42 24.4 3.5 Example 3 1.53 24.6 3.6 Example 4 1.48 24.8 3.8 Example 5 1.31 24.5 3.9 Example 6 1.49 24.2 3.9 Example 7 1.51 24.6 3.6 Example 8 1.42 24.7 3.6 Example 9 1.56 24.9 3.4 Example 10 1.33 24.0 3.6 Embodiment 11 1.59 24.6 3.6 Example 12 1.55 24.0 3.9 Comparative Example 1 1.20 24.9 3.3 Comparative Example 2 1.26 24.7 3.4
[0142] Table 3 Performance test results of sodium ion batteries prepared in various embodiments and comparative examples
[0143]
[0144]
[0145] It can be seen from Examples 1 to 12 and Comparative Examples 1 to 2 that the specific surface area A and skeleton density B of the negative electrode material subjected to twice carbon coating are significantly reduced. When the specific surface area A and the skeleton density B are controlled in the range of A×B<10, the negative electrode material of the present application has a lower skeleton density and compaction density, and a higher gram capacity, so that the sodium ion battery prepared therefrom obtains a higher energy density and an average discharge voltage.
[0146] It can be seen from Example 3 and Examples 11 to 12 that a lower activation temperature results in a larger skeleton density and a smaller closed-pore pore size, which leads to a decrease in closed-pore sodium storage capacity and a reduction in gram capacity; while a high activation temperature results in an excessively large closed-pore pore size of the negative electrode material, forming invalid pores, which affects the gram capacity and energy density of the battery; therefore, the closed-pore pore size of the negative electrode material also needs to be maintained within an appropriate range.
[0147] It can be seen from Examples 1, 2, 5, Examples 3, 6, 7 and Examples 7, 8 that the gram capacity of the battery can be adjusted by adjusting the hard carbon raw material; the negative electrode material after water vapor activation has a smaller skeleton density and a larger pore volume, and the gram capacity, battery density and average discharge voltage of the prepared battery are significantly improved.
[0148] The negative electrode material, preparation method and application thereof provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and embodiments of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for those skilled in the art, according to the idea of the present application, there will be changes in the specific embodiments and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A negative electrode material, wherein the specific surface area A and the true density B of the negative electrode material satisfy A×B<8; The specific surface area A of the negative electrode material is 0.5 m 2 / g-6m 2 / g.
2. The negative electrode material according to claim 1, characterized in that The specific surface area A and true density B of the negative electrode material satisfy A×B<6; Preferably, the specific surface area A and true density B of the negative electrode material satisfy A×B<4.
3. The negative electrode material according to claim 1, characterized in that The specific surface area A of the negative electrode material is 0.9 m 2 / g-5m 2 / g; Preferably, the specific surface area A of the negative electrode material is 1 m 2 / g-4m 2 / g.
4. The negative electrode material according to claim 1, characterized in that The true density B of the negative electrode material is 0.5 g / m 3 -1.45g / m 3 .
5. The negative electrode material according to claim 4, characterized in that The true density B of the negative electrode material is 0.8 g / m 3 -1.4g / m 3 ; Preferably, the true density B of the negative electrode material is 0.95 g / m 3 -1.3g / m 3 .
6. The negative electrode material according to any one of claims 1 to 5, characterized in that The negative electrode material comprises hard carbon, a carbon coating layer covering the hard carbon, and closed pores, wherein the closed pores are formed by the open pores formed by the carbon coating layer covering the outer surface of the hard carbon; Preferably, the closed pore volume accounts for more than 90% of the sum of all open pore volumes and closed pore volumes; Preferably, the closed pore volume accounts for more than 95% of the sum of all open pore volumes and closed pore volumes; Preferably, the closed pore volume accounts for more than 99% of the sum of all open pore volumes and closed pore volumes.
7. The negative electrode material according to claim 6, wherein the closed pore size of the negative electrode material is less than 3 nm; Preferably, the closed pore size of the negative electrode material is in the range of 0.1 nm to 3 nm; Preferably, the closed pore size of the negative electrode material is in the range of 0.5nm-3nm; Preferably, the closed pore size of the negative electrode material is in the range of 1 nm to 3 nm.
8. The negative electrode material according to any one of claims 1 to 5, wherein the negative electrode material satisfies at least one of the following conditions: (1) The negative electrode material I d / I g The range is 1.0-2.0; preferably, the negative electrode material I d / I g The range is 1.3-1.6; (2) The position of the diffraction peak in the X-ray diffraction spectrum of the negative electrode material is in the range of 20° to 30° at 2θ, and the half-peak width of the diffraction peak is 3° to 10°; preferably, the position of the diffraction peak of the negative electrode material is in the range of 24° to 25° at 2θ, and the half-peak width of the diffraction peak is 3° to 4°.
9. A sodium ion battery, characterized in that: The sodium ion battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; the negative electrode sheet comprises the negative electrode material as claimed in any one of claims 1 to 8.
10. An electronic device, characterized in that: Comprising the sodium ion battery as claimed in claim 9.
Citation Information
Patent Citations
Three-dimensional graphene and preparation method thereof
CN109336092A
Negative electrode active material, electrochemical device, and electronic device
CN115394999A
Sodium-ion battery hard carbon negative electrode material with high compaction density and low specific surface area and preparation method of sodium-ion battery hard carbon negative electrode material
CN117361496A
Negative electrode material and preparation method and application thereof
CN118352487A
Hard carbon material and preparation method thereof, negative plate, sodium ion battery and electric equipment
CN118645622A